Wanderers : a history of women walking - Andrews, Kerri, ....-; Jamie, Kathleen, 1962- (London : Reaktion Books, 2021)
This is a book about ten women over the past three hundred years who have found walking essential to their sense of themselves, as people and as writers. Wanderers traces their footsteps, from eighteenth-century parson's daughter Elizabeth Carter-who desired nothing more than to be taken for a vagabond in the wilds of southern England - to modern walker-writers such as Nan Sheperd and Cheryl Strayed. Offering a beguiling view of the history of walking, Wanderers guides us through the different ways of seeing - of being - articulated by these pathfinding women.
Keywords: Wandelen in de literatuur